2014
DOI: 10.4103/0970-0218.143023
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care availability in health centers of Mangalore taluk, India

Abstract: Background:Community-oriented oral health programs are seldom found in India. When primary health care systems were in the 1980s, dentistry was not adequately included. This has left oral health far behind other health services.Objectives:To find the availability of dental professionals, infrastructure, equipment, and treatments provided in health centers of Mangalore taluk.Materials and Methods:A cross-sectional study was conducted among medical officers and dentists working in all the health centers of Manga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Suboptimal primary health centers (PHCs): Although dental care is a part of primary health care in India, dental care services are available only in few states at the primary health care level. [60] Thus, general practitioners and health workers at PHCs function as the first point of contact for dental patients with an acute dental pain. Due to nonavailability of dentist in rural areas, patients approach these nondental practitioners to get temporary relief.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal primary health centers (PHCs): Although dental care is a part of primary health care in India, dental care services are available only in few states at the primary health care level. [60] Thus, general practitioners and health workers at PHCs function as the first point of contact for dental patients with an acute dental pain. Due to nonavailability of dentist in rural areas, patients approach these nondental practitioners to get temporary relief.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the level of independent variables related to the characteristics of the OHCTs and dental care available supplies, the results demonstrate that they are available to most OHCTs. A study in India noted that all the health centers that provided dental services possessed basic equipment both for identification of common oral diseases and for carrying out dental extractions and restorations, but preventive programs were not the focal point of the services provided ( Simon et al, 2014 ). In contrast, an African study showed that dental materials and equipment availability, skills of the practitioners, and the cost of services all play major roles toward provision and utilization of comprehensive oral care ( Nyamuryekunge et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding was reported in another study conducted in Mangalore where four PHCs did not have any government-appointed dentists but were managed by dentists from the private colleges in and around the area. [ 13 ] This is in contrast to the findings of a study done for the evaluation of Government Dental Centers in Egypt. [ 14 ]…”
Section: Discussionmentioning
confidence: 56%